(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
A fundamental tenet of the accounting profession is that accounting information is important forbusiness decision making. In virtually all small, medium or large companies accountinginformation is recorded, managed and often analysed in enterprise systems. Consequently wehave witnessed an increase in the importance and complexity of enterprise systems andbroadening in scope of the financial and non-financial information they provide. This shiftevidences that ‘many of the traditional, essential skills of professional accountants arebeing replaced by new technologies that are increasing in number and being rapidly developed. Accordingly as accountants increasingly use these systems to supportbusiness decision making, they must be educated in the operation of technologically enabledbusiness processes, including at the tertiary level.Pragmatism is a practical, matter-of-fact way of approaching or assessing situations or of solving problems